2022
DOI: 10.3389/fphys.2022.876078
|View full text |Cite
|
Sign up to set email alerts
|

Myostatin and its Regulation: A Comprehensive Review of Myostatin Inhibiting Strategies

Abstract: Myostatin (MSTN) is a well-reported negative regulator of muscle growth and a member of the transforming growth factor (TGF) family. MSTN has important functions in skeletal muscle (SM), and its crucial involvement in several disorders has made it an important therapeutic target. Several strategies based on the use of natural compounds to inhibitory peptides are being used to inhibit the activity of MSTN. This review delivers an overview of the current state of knowledge about SM and myogenesis with particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 182 publications
0
21
0
Order By: Relevance
“…Myostatin, as a muscle atrophy index, increases in the older population [ 7 ]. It binds to the activin type II receptor and suppresses muscle growth signaling pathways, protein synthesis, satellite cell activation, and negatively regulates myogenic differentiation and myofiber hypertrophy [ 8 , 9 ]. In contrast, follistatin as a member of the transforming growth factor-β family, blocking myostatin [ 4 ] and activating satellite cells [ 10 ], leading to hypertrophy and preventing age-associated muscle wastes.…”
Section: Introductionmentioning
confidence: 99%
“…Myostatin, as a muscle atrophy index, increases in the older population [ 7 ]. It binds to the activin type II receptor and suppresses muscle growth signaling pathways, protein synthesis, satellite cell activation, and negatively regulates myogenic differentiation and myofiber hypertrophy [ 8 , 9 ]. In contrast, follistatin as a member of the transforming growth factor-β family, blocking myostatin [ 4 ] and activating satellite cells [ 10 ], leading to hypertrophy and preventing age-associated muscle wastes.…”
Section: Introductionmentioning
confidence: 99%
“…This result indicates that MID-35 peptide was delivered to skeletal muscle as the intact form by ItP and the delivered MID-35 functioned in skeletal muscle. In previous reports, the weight of the tibialis anterior muscle was found to increase by a similar amount (1.33-fold) upon intramuscular injection of MID-35 [ 20 ], though it should be noted that the dose of MID-35 for ItP (75 nmol) was higher than that for intramuscular injection (30 nmol). Thus, we succeeded in increasing skeletal muscle weight by delivering MID-35 with the non-invasive intramuscular delivery technology ItP in this study.…”
Section: Discussionmentioning
confidence: 73%
“…Myostatin (growth differentiation factor-8, GDF-8) is a member of the transforming growth factor-β (TGF-β) superfamily and negatively regulates muscle growth by binding to activin type I and type II receptors and thus activating Smad 2/3 signaling [ 4 , 5 , 6 , 7 , 8 ]. Accordingly, myostatin inhibitors, including antibody, recombinant protein, and peptide, have been shown to be useful tools for inducing muscle growth, leading to the promising treatment of muscle atrophic disorders, such as muscular dystrophy, sarcopenia, and cancer-associated cachexia [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ]. However, clinical use for improving muscle wasting have not been achieved yet; hence, there is still room for the new strategies.…”
Section: Introductionmentioning
confidence: 99%
“…15,30,37 Several animal studies have shown that myostatin inhibition was associated with increased muscle mass and tumor regression. 15,30,37 Further studies are required to better understand the role and mechanism of muscle metabolism in cancer care.…”
Section: Discussionmentioning
confidence: 99%